Abstract concept formation in African grey parrots (Psittacus erithacus) on the basis of a low number of cues - Suková, Karolína; Uchytilová, Michaela; Lindová, Jitka (Behavioural processes, 2013)
The formation of the concept of sameness is considered as a crucial cognitive ability which allows for other high cognitive functions in some species, e.g. humans. It is often operationalized as transfer of the matching rule to new stimuli in a matching-to-sample task. Animal species show great differences regarding the number of stimuli needed in training to be able to perform a full transfer to new stimuli. Not only apes appear to master this task, but also corvids among the birds were shown to reach a full transfer using only few stimuli. Using colour, shape and number stimuli in a matching-to-sample design, we tested four grey parrots for their ability to judge identity. Only a limited set of 8 stimulus cards were used in training. Pairs of "same" number stimuli were visually different thus allowing to be matched according to number of elements only. All four parrots successfully transferred to testing phases including testing with completely new stimuli and their performance did not drop with new stimuli. Including number stimuli invalidated some interpretations based on visual non-abstract processes and give evidence for formation of the concept of sameness.
Keywords: nadání; Animals; vytváření pojmu; Aptitude; Concept Formation; Discrimination Learning; Female; podněty; diskriminační učení; zvířata; mužské pohlaví; Male; Cues; Parrots; papouškovití; ženské pohlaví